Justice, Dissent and the "War on Terrorism": Marcusean Musings on Militarism and Pacification - Oddie, Richard (UnderCurrents: Journal of Critical Environmental Studies, 2002)
In the wake of the September 11th attacks on the United States and the bombing of Afghanistan, those engaged in struggles for social and environmental justice are faced with a number of emerging problems and challenges.